2021
DOI: 10.4314/jasem.v25i8.37
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Heavy Metals in Soil, Water and Vegetables around Industrial area in Bauchi, Northeastern Nigeria

Abstract: This study examined the levels of heavy metals in soil, water, and vegetables (amaranthus, hibiscussabdariffa, and allium cepa leaves) around the industrial area Bauchi, Northeastern Nigeria. The composite samples of soil, water, and vegetables were collected and determine the level of heavy metals (Mn, Zn, Cd, Pb, and As) using Atomic Absorption Spectrophotometer (AAS). The level of the heavy metals decreased in the order of Mn > Zn > Pb > Cd, Pb > Zn > Mn > Cd, and Mn > Zn > Mn > C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
0
0
Order By: Relevance
“…TSS was measured using the gravimetric method. These findings agreed with [8], who reported higher TSS in dry months than in wet months in Gombe, Nigeria. The highest value (0.40-0.45 mg/l) was recorded in the dry season, while the lowest value (0.36-0.38 mg/l) occurred in the wet season.…”
Section: Total Suspended Solid (Tss)supporting
confidence: 92%
“…TSS was measured using the gravimetric method. These findings agreed with [8], who reported higher TSS in dry months than in wet months in Gombe, Nigeria. The highest value (0.40-0.45 mg/l) was recorded in the dry season, while the lowest value (0.36-0.38 mg/l) occurred in the wet season.…”
Section: Total Suspended Solid (Tss)supporting
confidence: 92%
“…The concentrations of Cu, Co, Cr and Cr in this research are far above what was reported in canned Tomato samples collected from Umuahia (Uroko et al, 2019). Sulaiman et al (2019) reported higher concentrations of Cd and Zn in Tomato samples produced in Gombe. Pb and Zn concentrations reported by Ndinwa et al (2014) in Tomato samples collected from Asaba also exceeded what was observed in this study.…”
Section: Results Of Chromium (Cr) Concentration In Tomato Samplescontrasting
confidence: 59%